The mitochondrial calcium uniporter regulates breast cancer progression via HIF‐1α - Anna Tosatto; Roberta Sommaggio; Carsten Kummerow; Robert B Bentham; Thomas S Blacker; Tunde Berecz; Michael R Duchen; Antonio Rosato; Ivan Bogeski; Gyorgy Szabadkai; Rosario Rizzuto; Cristina Mammucari (EMBO Molecular Medicine)
Abstract Triple‐negative breast cancer (TNBC) represents the most aggressive breast tumor subtype. However, the molecular determinants responsible for the metastatic TNBC phenotype are only partially understood. We here show that expression of the mitochondrial calcium uniporter (MCU), the selective channel responsible for mitochondrial Ca2+ uptake, correlates with tumor size and lymph node infiltration, suggesting that mitochondrial Ca2+ uptake might be instrumental for tumor growth and metastatic formation. Accordingly, MCU downregulation hampered cell motility and invasiveness and reduced tumor growth, lymph node infiltration, and lung metastasis in TNBC xenografts. In MCU‐silenced cells, production of mitochondrial reactive oxygen species (mROS) is blunted and expression of the hypoxia‐inducible factor‐1α (HIF‐1α) is reduced, suggesting a signaling role for mROS and HIF‐1α, downstream of mitochondrial Ca2+. Finally, in breast cancer mRNA samples, a positive correlation of MCU expression with HIF‐1α signaling route is present. Our results indicate that MCU plays a central role in TNBC growth and metastasis formation and suggest that mitochondrial Ca2+ uptake is a potential novel therapeutic target for clinical intervention.